(Why) Do Central Banks Care About Their Profits? - Igor Goncharov; Vasso Ioannidou; Martin C. Schmalz (Center for Economic Studies and ifo Institute (CESifo), 2017)
We document that central banks are significantly more likely to report slightly positive profits than slightly negative profits. The discontinuity in the profit distribution is (i) more pronounced amid greater political or public pressure, the public's receptiveness to more extreme political views, and agency frictions arising from governor career concerns, but absent when no such factors are present, and (ii) correlated with more lenient monetary policy inputs and greater inflation. These findings indicate that profitability concerns, while absent from standard theoretical models of central banking, are both present and effective in practice, and inform a theoretical debate about monetary stability and the effectiveness and riskiness of non-traditional central banking.
Keywords: E58; 330; central banks; profitability; non-traditional central banking; monetary stability